Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.53300/001c.6338
|View full text |Cite
|
Sign up to set email alerts
|

Is the Wounded Healer or the Psychologically Inflexible Healer in Undergraduate Psychology and Social Work Programs More Empathic or Willing to Violate Professional Boundaries?

Abstract: The term 'wounded healer' is sometimes used to describe people with a personal experience of adversity who enter a helping profession. Wounded healers have been thought to be both especially suited to counselling -perhaps through greater empathy for those in need -and at increased risk of making poor decisions due to the influence of their own psychopathology. Undergraduate students in psychology and social work (N=112) completed online questionnaires measuring childhood adversity, parentification, empathy, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…For mental health professionals, Dickeson et al (2020) found a significant positive relationship between ACEs and scores on the Sexual Boundary Violation Index (Swiggart et al, 2008), and for females, ACEs predicted Boundary Violation Propensity (Dickeson & Smout, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For mental health professionals, Dickeson et al (2020) found a significant positive relationship between ACEs and scores on the Sexual Boundary Violation Index (Swiggart et al, 2008), and for females, ACEs predicted Boundary Violation Propensity (Dickeson & Smout, 2018).…”
Section: Resultsmentioning
confidence: 99%